2021
DOI: 10.3389/fphys.2020.622466
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Neurological Manifestations: An Emerging Electroencephalographic Literature

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide since the end of year 2019 and is currently responsive for coronavirus infectious disease 2019 (COVID-19). The first reports considered COVID-19 as a respiratory tract disease responsible for pneumonia, but numerous studies rapidly emerged to warn the medical community of COVID-19-associated neurological manifestations, including encephalopathy at the acute phase and other postinfectious manifestations. Using standard visual anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 117 publications
1
16
1
1
Order By: Relevance
“…Many studies have reported that SARS-CoV-2 spike proteins can be detected in the brain. 45 , 46 Some studies have observed changes in EEG function, such as the distribution of EEG bands, structure of spectral entropy, and hemispheric connectivity. 25 , 26 Vellieux et al 45 showed that frontal EEG abnormalities could emphasize the hypothesis that SARS-CoV-2 enters the brain through olfactory structures and then spreads to the central nervous system via the frontal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that SARS-CoV-2 spike proteins can be detected in the brain. 45 , 46 Some studies have observed changes in EEG function, such as the distribution of EEG bands, structure of spectral entropy, and hemispheric connectivity. 25 , 26 Vellieux et al 45 showed that frontal EEG abnormalities could emphasize the hypothesis that SARS-CoV-2 enters the brain through olfactory structures and then spreads to the central nervous system via the frontal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential neuropathogenesis, neuroimaging studies on patients with COVID-19 and other respiratory infections are limited. Electroencephalography of patients with COVID-19 infection have shown frontal lobe abnormalities [13,14], while positron emission tomography (PET) of these patients has identified altered glucose metabolism in several brain areas. These include hypometabolism in the bilateral parahippocampal and fusiform gyri, left insula [15], dorsolateral prefrontal cortex, bilateral frontal eye fields and right anterior cingulate cortex, as well as hypermetabolism in the left orbitofrontal cortex, right posterior parietal cortex and right thalamus [16].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been reports of seemingly novel EEG abnormalities, specifically frontally predominant abnormalities, in patients hospitalized with acute COVID-19 infections [28,29]. However, based on an overall review of the literature to date, there is no EEG pattern that is specific for patients with neurological manifestations of COVID-19, and a more thorough investigation of these findings with attention to confounding variables is needed to establish correlation [28,[30][31][32]. Potential confounding variables include body positioning (prone vs supine positioning in ventilated ICU patients), imaging findings, and medical comorbidities.…”
Section: Eeg Findings Associated With Covid-19mentioning
confidence: 99%